Comparison of the efficacy of single vs. double autologous platelet-rich plasma intrauterine infusion on endometrial receptivity in thin endometrium patients: a prospective randomized controlled trial - Feng, Keng; Zhu, Lingling; Luo, Yudi; Ruan, Luhai; Li, Derong; Li, Xiang; Li, Ling; Wu, Ling (Frontiers in Endocrinology, 2025)
ObjectiveTo compare single versus double autologous platelet-rich plasma (PRP) intrauterine infusion effects on endometrial receptivity and pregnancy outcomes in patients with thin endometrium.MethodsThis randomized controlled trial included 100 patients with thin endometrium and infertility, assigned to single (n=50) or double (n=50) infusion groups. The single group received 1.0 ml of PRP on day 11 of the hormone replacement therapy-frozen embryo transfer (HRT-FET) cycle, while the double group received 1.0 ml on both days 11 and 13. Primary outcomes included endometrial thickness, receptivity changes, and clinical pregnancy rates; secondary outcomes were cycle cancellation rate, miscarriage rate, and endometrial hemodynamics. Statistical analysis was conducted using SPSS 26.0.ResultsThe double PRP infusion group exhibited measurable improvements in endometrial and early pregnancy outcomes. 1) Endometrial thickness increased (8.42 ± 0.53 mm vs 7.96 ± 0.45 mm, P<0.01); 2) Hemodynamic parameters improved for resistance index (RI) (1.72 ± 0.08 vs 1.79 ± 0.08, P<0.01) and pulsatility index (PI) (3.83 ± 0.64 vs 4.38 ± 0.68, P<0.01); 3) Clinical outcomes: lower cycle cancellation rate (10.0% vs 26.0%, P=0.037) and higher clinical pregnancy rate (48.9% vs 27.0%, P=0.043).However, early miscarriage rates were similar between groups (p > 0.99).ConclusionCompared to a single intrauterine infusion, double intrauterine PRP infusion may enhance the receptivity of a thin endometrium and improve clinical pregnancy outcomes. However, since the study population did not include patients with thin endometrium who also have a history of recurrent implantation failure or recurrent miscarriage, caution is advised when applying these findings to this specific group. Furthermore, these conclusions require validation through larger, randomized, multicenter trials.